Analisis Nilai Tambah Produksi pada Industri Tempe Di Kecamatan Barabai Kabupaten Hulu Sungai Tengah - Azwar Saihani (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
This research has two objectives, namely to determine soybean industry overview in sub Barabai and calculating the amount of value added generated by the soybean industry in the Barabai District Hulu Sungai Tengah Regency. The research was conducted at tempe existing tempe industrial business in the District Barabai Hulu Sungai Tengah Regency. The method used in analyzing the data available from industry employers in the Barabai District Hulu Sungai Tengah is to use the formula of gross value added, net value added, and value-added raw materials. The calculations associated with the equipment used, the main raw material, and auxiliary raw materials used in the process of making tempe. Based on the results of research conducted on the existing soybean industry in the District Barabai gross value added generated from all respondents of Rp 56.247.500, net value added generated amounted to Rp 48.062.500, while for value-added raw materials amounting to Rp 125.363/Kg. The existence of the soybean industry in Barabai be able to increase the added value for entrepreneurs tempe